2017
DOI: 10.1186/s12906-017-1603-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an L-arginine-based multi ingredient product on endothelial function in subjects with mild to moderate hypertension and hyperhomocysteinemia - a randomized, double-blind, placebo-controlled, cross-over trial

Abstract: BackgroundNutrition plays an important role in prevention and management of cardiovascular diseases (CVD) in early stages. Recent research demonstrated beneficial effects of various nutritional ingredients on vascular health. The aim of the current study was to evaluate the effects of an L-arginine-based multi ingredient product (AbMIP) on vascular function.MethodsTwenty-five male and female subjects, aged between 45 and 65 years with elevated blood pressure and hyperhomocysteinemia were included in this cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 28 publications
1
49
0
1
Order By: Relevance
“…Endothelial dysfunction is the first step leading from decreased vascular dilatation up to hypertension and other cardiovascular disorders. This fact was confirmed not only in experimental (Liu et al , 2017 ) but also in clinical studies (Reule et al , 2017 ) and is in accordance with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Endothelial dysfunction is the first step leading from decreased vascular dilatation up to hypertension and other cardiovascular disorders. This fact was confirmed not only in experimental (Liu et al , 2017 ) but also in clinical studies (Reule et al , 2017 ) and is in accordance with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…HHcy promotes oxidative stress, which induces endothelial dysfunction leading to atherosclerosis and other cardiovascular diseases. Clinical in vivo studies have confirmed the occurrence of endothelial dysfunction in HHcy . To assess a potential mechanism of the effect of HHcy on cardiac function, we measured oxidative stress indicators and the activity of the antioxidant enzyme system (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis indicates that doses between 4 and 24 g/day decrease blood pressure (systolic, 5 mmHg; diastolic, 3 mmHg) (240). Other recent studies show improved endothelial function and insulin sensitivity in patients with impaired glucose uptake and metabolic syndrome (6.6 g/day L-arginine for 2 wk) (663) and improved endothelial function and decreased homocysteine levels in patients with elevated blood pressure and hyperhomocysteinuria (2.4 g/day for 4 wk) (781).…”
Section: Pharmacological Interventions In Enos Uncouplingmentioning
confidence: 94%